Safety, tolerability, and pharmacodynamics of an anti-interleukin-1α/β dual variable domain immunoglobulin in patients with osteoarthritis of the knee: a randomized phase 1 study. Issue 12 (December 2017) - Wang, S.X.; Abramson, S.B.; Attur, M.; Karsdal, M.A.; Preston, R.A.; Lozada, C.J.; Kosloski, M.P.; Hong, F.; Jiang, P.; Saltarelli, M.J.; Hendrickson, B.A.; Medema, J.K.
Summary: Objective: To investigate the safety, tolerability, pharmacokinetics, and pharmacodynamics of ABT-981, a human dual variable domain immunoglobulin simultaneously targeting interleukin (IL)-1α and IL-1β, in patients with knee osteoarthritis (OA). Method: This was a randomized, double-blind, placebo-controlled, single-center study of multiple subcutaneous (SC) injections of ABT-981 in patients with mild-to-moderate OA of the knee (NCT01668511). Three cohorts received ABT-981 (0.3, 1, or 3 mg/kg) or placebo every other week for a total of four SC injections, and one cohort received ABT-981 (3 mg/kg) or placebo every 4 weeks for a total of three SC injections. Assessment of safety and tolerability were the primary objectives. A panel of serum and urine biomarkers of inflammation and joint degradation were evaluated. Results: A total of 36 patients were randomized (ABT-981, n  = 28; placebo, n  = 8); 31 (86%) completed the study. Adverse event (AE) rates were comparable between ABT-981 and placebo (54% vs 63%). The most common AE reported with ABT-981 vs placebo was injection site erythema (14% vs 0%). ABT-981 significantly reduced absolute neutrophil count and serum concentrations of IL-1α/IL-1β, high-sensitivity C-reactive protein, and matrix metalloproteinase (MMP)-derived type 1 collagen. Serum concentrations of MMP-derived type 3 collagen and MMP-degraded C-reactive protein demonstrated decreasing trends with ABT-981. Antidrug antibodies were found in 37% of patients but were not associated with the incidence or severity of AEs. Conclusion: ABT-981 was generally well tolerated in patients with knee OA and engaged relevant tissue targets, eliciting an anti-inflammatory response. Consequently, ABT-981 may provide clinical benefit to patients with inflammation-driven OA.